The Effect of Cash Turnover, Accounts Receivable Turnover, and the Number of Credit Customers on the Profitability (ROA) of Village Credit Institutions (LDP) in Negara District in 2021-2023 - Kadek Surya Trisnanda; Putu Lidia Marini; I Gusti Agung Sasih Gayatri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the effect of cash turnover, receivables turnover, and the number of credit customers on profitability. This study was conducted at 10 LPDs registered at the LPLPD office in Jembrana Regency. This study is quantitative, using secondary data sourced from the LPD financial statements for 2021-2023. The data analysis technique used was multiple linear regression analysis. The results of the analysis indicate that partially, cash turnover has a positive and significant effect on profitability, receivables turnover has a negative but insignificant effect on profitability, and the number of credit customers has a positive and significant effect on profitability. Simultaneously, cash turnover, receivables turnover, and the number of credit customers simultaneously affect profitability (ROA) at LPDs in Negara District.